Petiole Sampling as a Tool for In-Season Nitrogen Management in Cotton - Akash Shah; Hardeep Singh; Lakesh Sharma; Ethan Carter; Guilherme Morata (EDIS, 2025)
This publication aims to guide cotton producers, Extension agents, crop advisors, and consultants on the correct method of petiole sampling for nitrate-nitrogen analysis and interpretation of petiole nitrate-nitrogen test results, and also discusses ways in which monitoring petiole nitrate-nitrogen concentration can be used as a tool for effective in-season N management in cotton. Written by Akash Shah, Hardeep Singh, Lakesh Sharma, Ethan Carter, and Guilherme Morata, and published by the UF/IFAS Department of Agronomy, June 2025.